Language, Performance, Memory and Transculturation in the Jocs Florals Catalans of Cuba - Jerez Columbi?, Yairen (Environmental Protection Agency, 2022)
This article studies the role of language, literature and performance in the consolidation of the Catalan community of Cuba, particularly through the literary prize Jocs Florals Catalans of Havana, celebrated in 1923 and 1944. Relying on Fernando Ortiz’s (1940/1978) concept of transculturation and Joseph Roach’s (1996) approach to circum-Atlantic performances, which shows how the memories of particular times and spaces are embodied and travel in and through performance, the article discusses how these events transmitted ideas of Catalan culture and exemplified the ties and tensions between nationalist narratives and the transculturation of identities in Cuba during the first half of the twentieth century. In order to illustrate the different, yet complementary meanings of the two events, the article examines the simultaneous celebration of the Jocs Florals in Havana and Barcelona in 1923 and the impact of the mass exile of pro-Republican communities in the aftermath of the Spanish Civil War in the literary prize of 1944, twenty years after the first event.
PUBLISHED
Keywords: Language; Performance; Memory; Transculturation; Nationalism; Exile; Catalonia; Migration; Cuba; Jocs Florals Catalans; Caribbean Studies; Catalan Studies; Intercultural Communication; Intercultural Communications; Latin American Studies; MIGRATION; PERFORMANCE; cultural translation; literary translation; transnational migration